Vitamins Reverse Endothelial Dysfunction Through Regulation of eNOS and NAD(P)H Oxidase Activities - Ulker, Sible; McKeown, Pascal; Bayraktutan, Ulvi (American Heart Association, 2003)
Antioxidant vitamins C and E have protective properties in genetic hypertension associated with enhanced oxidative stress. This study investigated whether vitamins C and/or E modulate vascular function by regulating enzymatic activities of endothelial nitric oxide synthase (eNOS) and NAD(P)H oxidase using thoracic aortas of 20- to 22-week-old male spontaneously hypertensive rats (SHR) and their matched normotensive counterparts, Wistar-Kyoto rats (WKY). SHR aortas had impaired relaxant responses to acetylcholine but not to sodium nitroprusside, despite an 2-fold increase in eNOS activity and NO release. The levels of superoxide anion (O2 ), a potent NO scavenger, and NAD(P)H oxidase activity were also 2-fold higher in SHR aortas. Mechanical but not pharmacological inactivation of endothelium (by rubbing and 100 mol/L L-NAME, respectively) significantly abrogated O2 in both strains. Treatments of SHR aortas with NAD(P)H oxidase inhibitors, namely diphenyleneiodinium and apocynin, significantly diminished O2 production. The incubation of SHR aortas with different concentrations of vitamin C (10 to 100 mol/L) and specifically with high concentrations of vitamin E (100 mol/L) improved endothelial function, reduced superoxide production as well as NAD(P)H oxidase activity, and increased eNOS activity and NO generation in SHR aortas to the levels observed in vitamin C- and E-treated WKY aortas. Our results reveal endothelial NAD(P)H oxidase as the major source of vascular O2 in SHR and also show that vitamins C and E are critical in normalizing genetic endothelial dysfunction through regulation of eNOS and NAD(P)H oxidase activities.